The Verb In Nyakyusa: A Focus On Tense, Aspect And Modality - Persohn, Bastian (My University, 2020)
Nyakyusa is an under described Bantu language spoken by around 800.000 speakers in the Mbeya Region of Tanzania. This book provides a detailed description of the verb in this language. The topics covered include the complex morphophonological and morphological processes as well as verb-to-verb derivation, copula verbs and grammaticalized verbs of motion. The main body of the book consists of a detailed description of tense, aspect and modality constructions, which includes not only an in-depth discussion of their sentence level semantics, but also of their patterns of employment in discourse. This is the second, slightly revised edition.
Keywords: Nyakyusa; Bantu language; Verb